Uninformed : why people know so little about politics and what we can do about it - Lupia, Arthur, 1964- (Oxford University Press, 2016)
In this capstone work, eminent political scientist Arthur Lupia synthesizes years of work with scientists and educators in all arenas to figure out how to increase issue competence among voters.